Protonation and H/D exchange reactions promoted by a sulfur-rich osmium hydride complex: identification of a labile dihydrogen complex. - Heinemann, Frank Wilhelm; Sellmann, Dieter; Prakash, R. (Dalton Transactions, 2004)
The sulfur-rich osmium nitrosyl complexes Bu(4)N[Os(NO)((bu)S(2))(2)] (1) [(bu)S(2)(2-) = 3,5-tert-butyl-1,2-benzenedithiolate(2-)] and [Os(NO)(py(bu)S(4))]Br ()[py(bu)S(4)(2-) = 2,6-bis(2-sulfanyl-3,5-di-tert-butylphenylthio)dimethylpyridine(2-)] have been synthesized. The molecular structure of 1 exhibits a square-pyramidal geometry with the NO group at the apical position. A pseudo-octahedral geometry with two thiolate and two thioether donors in trans configuration is found for 2. Compound 2 shows two quasi-reversible one-electron redox waves at E(1/2) = 0.51 and -0.46 V vs. NHE for the redox couples [Os(NO)(py(bu)S(4))](+1/0) and [Os(NO)(py(bu)S(4))](0/-1), respectively. 2 reacts with NaAlH(4) to produce Na[Os(H)(py(bu)S(4))] (3), which exhibits a typical hydride resonance in the (1)H NMR spectrum at delta =-15.03 ppm. Protonation of 3 with HBF(4)/CD(3)OD at 20 degrees C rapidly releases H(2)/HD to afford the dinuclear complex [Os(py(bu)S(4))](2) (4). Low temperature (1)H and (2)H NMR spectra of in [D(8)]THF with CH(3)OH or CD(3)OD at -80 degree C allow the observation of the formation of [Os(H(2)/HD)(py(bu)S(4))]. A 1 : 1 : 1 triplet at delta = -7.84 ppm [J(HD) = 31.2 Hz] and a relaxation time of T(1)(min) = 6 ms (-65 degrees C, 270 MHz) firmly establish the presence of eta(2)-H(2)/HD ligand. At room temperature, 3 interacts with D(2) (1 atm) and undergoes heterolytic D(2) cleavage followed by H/D exchange to form Na[Os(D)(py(bu)S(4))] (3a). A plausible cyclic mechanism has been proposed.